DAMPAK KEBIJAKAN SURAT PERNYATAAN TANGGUNG JAWAB MUTLAK PERATURAN MENTERI DALAM NEGERI NOMOR 9 TAHUN 2016 TERHADAP PENCATATAN PERKAWINAN: Impact of The Policy Statement of Absolute Responsibility Regulation of The Minister of Homeland Number 9 of 2016 on Marriage Registration - Sri Nanang Meiske Kamba; Nur Mohamad Kasim (Jurnal Hukum PRIORIS, 2023)
Marriage registration is an official process that involves registering and documenting a couple's marriage at authorized institutions, such as the Office of Religious Affairs (KUA) and the Population and Civil Registry Service. This process legally and administratively records marriage events, producing an official document stating the couple's marital status. This research uses normative research with a focus on studying legal norms relating to marriage registration. The analysis used is a qualitative descriptive approach using legislation (statute approach) to analyze the issues that arise in connection with the Statement of Absolute Responsibility and its impact on marriage registration and the legality of marriages after the SPTJM policy. The research results show that the Statement of Absolute Responsibility policy has a positive impact, such as providing facilities for producing children's birth certificates and other documents. However, this policy can also present complexities related to the status of "Unregistered Marriage," which raises legal issues, protecting the rights of wives and children, as well as law enforcement against the practice of polygamy and polyandry. Even though the information of couples who are mar ried in an unregistered marriage is recorded in the Family Card document of the Population and Civil Registry Office, recognition is still required before the law so that this couple has adequate legal standing in court to ensure the validity of their marriage. Keywords: Impact, SPTJM Policy, Marriage Registration